Konstitusionalitas Penempatan Anggota Polri pada Jabatan Sipil: Analisa Putusan MK Nomor 15/Puu-Xx/2022 - Fairuz Nasywa Dien; Try Intan Febriana Magdalena; Yohanes Brilian Jemadur; Sherliana Ika Pratiwi (Jurnal Hukum Lex Generalis, 2025)
Pursuant to Article 28(3) of Law No. 2 of 2002 on the National Police of the Republic of Indonesia, it is stipulated that members of the National Police may only hold positions outside the institution after retiring or resigning. However, this provision becomes ambiguous when considered alongside the Civil Servant Law, the Government Regulation on Civil Servant Management, and Article 201 of Law No. 10 of 2016 on Regional Head Elections, which allow members of the Indonesian National Armed Forces (TNI) and the Indonesian National Police (Polri) to serve as acting regional heads. These overlapping and inconsistent regulations create legal uncertainty, particularly when members of the Indonesian National Police (Polri) occupy strategic civilian positions. The findings indicate that the Constitutional Court upholds such appointments provided they meet legal requirements. However, the dominance of the central government and the lack of public participation raise concerns regarding the principles of democracy and regional autonomy. More transparent, participatory and comprehensive regulations are needed.